The Energy Consumption Comparison of Temperature Difference-based Defrosting Exit Method and Time-based Defrosting Exit Method with Various Static Pressure Differences (Journal of Solar Energy Research Updates, 2024)
The time-based defrosting exit method(TDEM) has been widely used in cold storage, but the issue of energy consumption has been heavily criticized. In this paper, a temperature difference-based defrosting exit method(TDDEM) is proposed to compare with TDEM. Firstly, a parameter acquisition system of cold storage is constructed, and the experimental setup is conducted to determine the experimental parameters. Subsequentially, the range of defrosting static pressure difference is determined based on pre-frosting experiment, and the defrosting experiment of TDEM and TDDEM are carried out at five various static pressure difference conditions, 16Pa, 14Pa, 12Pa, 10Pa and 8Pa, respectively. The results show that the temperature fluctuations per defrosting events of TDEM are more severe compared to TDDEM, with with average increases of 102.2%, 91.6%, 59.3%, and 46.5%, respectively. Energy consumptions of TDDEM are markedly lower than TDEM, with reductions of 21.4%, 15.7%, 14.09% and 14.59%, respectively. Whether TDEM or TDDEM, the lowest energy consumption is occurred at 10Pa, and highest is 8Pa.